2001
DOI: 10.3141/1744-03
|View full text |Cite
|
Sign up to set email alerts
|

Measuring the Level of Services at Airport Passenger Terminals: Comparison of Perceived and Observed Time

Abstract: A mathematical model to measure the level of service at airport passenger terminals is presented. The model relates passengers’ ratings of services at terminals and the time spent waiting for those services. The fuzzy concept is used to deal with the vagueness of service ratings such as “satisfied” and “unsatisfied.” Furthermore, two instruments are used to obtain the amount of time spent in service processes: perceived time reported by passengers and objective quantities measured by researchers. Empirical dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 2 publications
(1 reference statement)
0
20
0
Order By: Relevance
“…For example see,Mu¨ller and Gosling (1991),Lemer (1992),Davis and Braaksma (1987),Yen (1995),Yen et al (2001),Omer and Khan (1988),Ashford (1988),Ndoh and Ashford (1993),Seneviratne and Martel (1994),Caves and Pickard (2001), andPark (1999).…”
mentioning
confidence: 96%
“…For example see,Mu¨ller and Gosling (1991),Lemer (1992),Davis and Braaksma (1987),Yen (1995),Yen et al (2001),Omer and Khan (1988),Ashford (1988),Ndoh and Ashford (1993),Seneviratne and Martel (1994),Caves and Pickard (2001), andPark (1999).…”
mentioning
confidence: 96%
“…Many researchers have pointed out that customers' perceived service levels differ significantly from actual service levels (Mishalani et al 2006;Yen, Teng, and Chen 2001). Mishalani et al (2006) found perceived waiting time at bus stops to be greater than the actual waiting time in the range of 3-15 minutes due to the absence of accurate real-time bus arrival information.…”
Section: Methodsmentioning
confidence: 95%
“…Nevertheless, Ashford (1988) suggested that a strong interaction exists between space provision and time; however, that interaction cannot be obtained by the P-R concept as it has been presented. 1 In addition to that deficiency, recent LOS studies of airport passenger terminal processing components have shown that perceived and actual times have enormous discrepancies (Park, 1994(Park, , 1999Yen et al, 2001). Those discrepancies indicate that obtaining data by the stated preference technique must be used with caution.…”
Section: Previous Studiesmentioning
confidence: 93%